The Effect of Initial Oxygenation on Hemodynamic Stability of Trauma Patients in the Emergency Department - Agnes Batmomolin (International Journal of Health Sciences, 2025)
Background:Trauma patients presenting to the Emergency Department (ER) often experience hemodynamic instability due to bleeding, hypoxia, and the acute stress response. Early oxygenation is a priority intervention in the management of trauma patients to prevent tissue hypoxia and maintain hemodynamic stability. Objective:This study aims to determine the effect of early oxygenation on the hemodynamic stability of trauma patients in the emergency room. Method:This study used a quasi-experimental design with a pretest–posttest approach without a control group. The study sample consisted of 40 trauma patients selected using a purposive sampling technique. Hemodynamic parameters measured included blood pressure, pulse rate, respiratory rate, and oxygen saturation before and after initial oxygenation. Data analysis used a paired t-test with a significance level of p < 0.05. Results:The results of the study showed a significant increase in the hemodynamic stability of trauma patients after initial oxygenation (p < 0.05). Conclusion:Early oxygenation administration has a significant effect on the hemodynamic stability of trauma patients in the ER.